Multidisciplinary treatment of obstructive left colon cancer - Guan Helong; Bai Minghan; Sun Lingyu (结直肠肛门外科)
The value of multidisciplinary treatment (MDT) has been recognized for diagnosing and treating colorectal cancer. Diagnosis and treatment for obstructive left colon cancer has undergone from surgical model to MDT. This review discusses MDT for obstructive left colon cancer, such as the sequencing of surgery and chemotherapy, concurrent or staged surgery, colostomy or stenting, and the choice of nutritional treatment and formulas. The ideal treatment model of obstructive left colon cancer should be stent placement followed by neoadjuvant chemotherapy or neoadjuvant immunotherapy, the shift from emergency operation to confine operation, and concomitant nutritional support to ensure successful implementation of the treatment plan.